2003
DOI: 10.1128/jvi.77.19.10623-10629.2003
|View full text |Cite
|
Sign up to set email alerts
|

Significance in Replication of the Terminal Nucleotides of the Flavivirus Genome

Abstract: Point mutations that resulted in a substitution of the conserved 3-penultimate cytidine in genomic RNA or the RNA negative strand of the self-amplifying replicon of the Flavivirus Kunjin virus completely blocked in vivo replication. Similarly, substitutions of the conserved 3-terminal uridine in the RNA negative or positive strand completely blocked replication or caused much-reduced replication, respectively. The same preference for cytidine in the 3-terminal dinucleotide was noted in reports of the in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 52 publications
3
68
0
1
Order By: Relevance
“…The multiple functions of the 3Ј-SL in viral replication and the pleiotropic effect of the mutations introduced could explain our observations. In this regard, the results are in agreement with previous studies that have shown an essential function of the last nucleotides of flavivirus genomes (25,26,41). Therefore, to further understand the complex process of the structural changes around the 3Ј-SL during viral replication in infected cells, more information about the multiple functions of the 3Ј-SL is necessary.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…The multiple functions of the 3Ј-SL in viral replication and the pleiotropic effect of the mutations introduced could explain our observations. In this regard, the results are in agreement with previous studies that have shown an essential function of the last nucleotides of flavivirus genomes (25,26,41). Therefore, to further understand the complex process of the structural changes around the 3Ј-SL during viral replication in infected cells, more information about the multiple functions of the 3Ј-SL is necessary.…”
supporting
confidence: 81%
“…24), the mechanism by which this element controls RNA synthesis is still unclear. Specific bulges within the 3Ј-SL as well as nucleotides at the loop and the 3Ј terminal sequence were found to be essential for RNA replication (25)(26)(27)(28). The 5Ј bottom part of the large stem of the 3Ј-SL contains the 3Ј-UAR sequence, complementary to the 5Ј-UAR region of the 5Ј-UTR (12,13,21).…”
Section: Dengue Virus (Denv)mentioning
confidence: 99%
“…29). The 3Ј-terminal ϳ95 nt of these viruses form a conserved SL structure that in the upper loop carries the highly conserved pentanucleotide motif CACAG that at least for Kunjin virus was shown to be crucial for RNA replication (18). Given this high conservation between different flaviviruses, we assume that cellular proteins that are expressed in various tissues and conserved between different species are involved in the formation of a replication complex at the 3Ј end of these genomes.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is based on in vitro transcription studies using RdRp from bacteriophage Q␤, Turnip yellow mosaic virus, and TCV (67,68). Studies on flaviviruses and bromoviruses have also indicated that some or all of the 3Ј-terminal nucleotides are critical for replication in vivo and transcription in vitro (3,25,37,(49)(50)(51), although these nucleotides may not be important for stable interaction between the RdRp and the template (9). Despite the ability of TCV RdRp to initiate opposite the penultimate C in a sequence containing CCA repeats (68), the 3ЈCCC on the natural satC template is dispensable for basic transcription in vitro (20).…”
Section: Discussionmentioning
confidence: 99%